Factors in Vaccine Refusal by Patients Applying for COVID-19 PCR Test - Ferhat ARSLAN; Behcet AL; Gorkem Alper SOLAKOGLU; Omer Faruk GULSOY; Cagatay NUHOGLU; Sema AYTEN (Medeniyet Medical Journal)
Objective: This study was designed to determine the reasons for vaccine rejection in patients who applied for the coronavirus disease-2019 (COVID-19) polymerase chain reaction (PCR) test but did not receive the vaccine. Methods: The study was conducted prospectively in the emergency department of a tertiary hospital between 31.01.2022 and 31.05.2022. 1000 patients who applied for the COVID-19 PCR test and refused to be vaccinated were included. The COVID-19 status of the participants, reasons for their application, number of PCR tests, methods of obtaining information about the vaccine, and reasons for the rejection of the vaccine were questioned. Results: 54.6% of the participants were male and 45.4% were female. 60.7% of the patients applied for testing due to symptoms, 25.4% due to contact with people with symptoms, and 23.9% due to travel. 43.3% of the cases had COVID-19 infection; 53.6% of them had tested an average of 2-5 times in the last year. Most of the information about the vaccine was taken from social media, television, medical publications, and people around, respectively. Of the participants, 62.0% believed that COVID-19 vaccines had side effects, 47.3% believed that it had no protection, and 30.9% believed that there was not enough study on the subject. As the age grew, the rate of learning information from social media increased. Conclusions: The most common reasons for COVID-19 vaccine rejection were vaccine side effects, doubtful vaccine protection, and concerns about the lack of sufficient studies on the vaccine. The higher the education level, the higher the vaccine rejection rate.